Suppressor U1 snRNAs in Drosophila. - Lo, P C; Roy, D; Mount, S M (Genetics, 1994)
Although the role of U1 small nuclear RNAs (snRNAs) in 5' splice site recognition is well established, suppressor U1 snRNAs active in intact multicellular animals have been lacking. Here we describe suppression of a 5' splice site mutation in the Drosophila melanogaster white gene (wDR18) by compensatory changes in U1 snRNA. Mutation of positions -1 and +6 of the 5' splice site of the second intron (ACG[GTGAGT to ACC]GTGAGC) results in the accumulation of RNA retaining this 74-nucleotide intron in both transfected cells and transgenic flies. U1-3G, a suppressor U1 snRNA which restores base-pairing at position +6 of the mutant intron, increases the ratio of spliced to unspliced wDR18 RNA up to fivefold in transfected Schneider cells and increases eye pigmentation in wDR18 flies. U1-9G, which targets position -1, suppresses wDR18 in transfected cells less well. U1-3G,9G has the same effect as U1-3G although it accumulates to lower levels. Suppression of wDR18 has revealed that the U1b embryonic variant (G134 to U) is active in Schneider cells and pupal eye discs. However, the combination of 9G with 134U leads to reduced accumulation of both U1b-9G and U1b-3G,9G, possibly because nucleotides 9 and 134 both participate in a potential long-range intramolecular base-pairing interaction. High levels of functional U1-3G suppressor reduce both viability and fertility in transformed flies. These results show that, despite the difficulties inherent in stably altering splice site selection in multicellular organisms, it is possible to obtain suppressor U1 snRNAs in flies.
Keywords: Alternative Splicing; Animals; Base Sequence; Cell Line; Cell Nucleus; DNA Primers; Drosophila melanogaster; Female; Genes, Suppressor; Genetic Variation; GENOTYPE; Introns; Male; Molecular Sequence Data; Mutagenesis, Site-Directed; Nucleic Acid Conformation; Oligodeoxyribonucleotides; PHENOTYPE; Recombinant Proteins; Ribonucleoprotein, U1 Small Nuclear; RNA, Small Nuclear; Transfection; Transformation, Genetic